Perancangan tas handphone bergaya minimalis berbahan kulit: Studi kasus Aleta Leather - Wulandhari, Rigita; Sutianah, Cucu; Insani, Handayani Madania (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2025)
Aleta Leather consumers tend to make product payments using QR codes on their smartphones, creating a need for a specialized phone bag. This study aims to apply design aspects to a phone bag with a minimalist image that aligns with consumer preferences. The research employs a semantic differential approach to identify consumers’ perceptions of minimalist imagery based on elements of line, shape, volume, color, texture, and features, collected through an online questionnaire. The findings indicate that the appropriate phone bag design incorporates curved lines on the side edges, a rectangular shape, a slightly bulging volume, a Havana color tone, and an orange chrome leather texture. The main components include a phone slot, three internal card slots, and a compartment for cash. The novelty of this study lies in the application of semantic differential analysis in designing a minimalist phone bag based on consumer preferences, while maintaining the brand’s identity. Based on the findings, consumer recommendations for further development include expanding the card slot feature and adjusting the main pocket’s width to better accommodate user needs, as smartphones have become a primary necessity in daily life.